Dosing Pattern and Early Cumulative Dose of Liposomal Irinotecan in Metastatic Pancreatic Cancer: A Real-World Multicenter Study - Su, Yung-Yeh; Chiang, Nai-Jung; Li, Chung-Pin; Yen, Chia-Jui; Yang, Shih-Hung; Chou, Wen-Chi; Chen, Jen-Shi; Chiu, Tai-Jan; Chen, Yen-Yang; Chuang, Shih-Chang; Bai, Li-Yuan; Chiu, Chang-Fang; et al. (Frontiers in Oncology, 2022)
Introduction: This multicenter, real-world cohort study aimed to evaluate the effectiveness of early cumulative dose administration and dosing pattern of liposomal irinotecan plus fluorouracil/leucovorin (nal-IRI+5-FU/LV) in patients with gemcitabine-refractory metastatic pancreatic ductal adenocarcinoma (mPDAC). Material and Methods: Electronic medical records of mPDAC patients treated with nal-IRI+5-FU/LV in nine participating centers were manually reviewed. To accommodate to NAPOLI-1 study population, only patients with an Eastern Cooperative Oncology Group Performance Score (ECOG PS) 0-1 were included. The survival impact of the relative 6-week cumulative dose and dosing pattern (standard vs. reduced starting dose, with and without further dose modification) was investigated. Results: Of the 473 included patients, their median overall survival (mOS) was 6.8 [95% CI, 6.2-7.7] months. The mOS of patients who received a relative 6-week cumulative dose of >80%, 60-80% and <60% were 7.9, 8.2 and 4.3 months, respectively (p<0.0001). Their survival impact remained significant after covariate adjustment using Cox regression. The mOS was 8.0-8.2 months in patients with standard starting dose with and without early dose modification, and 9.3 and 6.7 months in those who had reduced starting dose with and without escalation in the subsequent treatment, respectively. The incidence of grade 3-4 neutropenia and diarrhea was 23.3% and 2.7%, respectively. Conclusion: Our results support the use of nal-IRI+5-FU/LV in gemcitabine-refractory mPDAC and suggest that a lower starting dose followed by a re-escalation strategy could achieve clinical outcomes comparable to those with standard starting doses in real-world practice.